TEACHER CENTERED LEARNING & STUDENT CENTERED LEARNING (SCL) - Muhammad Hafid Hafid; Mardia hayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of modern education demands a paradigm shift from teachercentered learning (TCL) to student-centered learning (SCL). This paper aims to examine the concepts, characteristics, roles of teachers and students, as well as the strengths and challenges of implementing TCL and SCL in the learning process, particularly in Islamic Religious Education (PAI). This study employs a library research method by analyzing relevant books and scholarly journal articles. The discussion indicates that TCL is effective in classroom control and efficient content delivery; however, it tends to limit students’ active participation and learning independence. In contrast, SCL positions students as active subjects in the learning process, encouraging the development of critical, creative, collaborative, and independent learning skills. Nevertheless, the implementation of SCL faces several challenges, including teachers’ readiness, students’ learning autonomy, and the availability of supporting facilities and learning culture. Therefore, careful planning and collaboration among teachers, students, and educational institutions are essential to ensure the effective and sustainable implementation of SCL in improving the quality of learning. Keywords: Teacher-Centered Learning, Student-Centered Learning, learning paradigm, modern education.